Coronary Artery Phase agreement of CT and X-ray angiogram images through Non-Rigid Registration - Son Jin Won; SIYEOP YOON; Lee, Deukhee (2017 17th International Conference on Control, Automation and Systems (ICCAS 2017), 2017)
Percutaneous coronary intervention (PCI) procedure is a universal treatment for Chronic total occlusion (CTO). During PCI procedure, X-ray angiogram image is used to find a catheter and CTO region. However, because the angiogram image is 2D and heart beats, it is hard to find CTO region in real-time using angiogram image. In this paper, we proposed a novel method to visualize CTO region onto angiogram image using biplane angiogram image and CT image through non-rigid registration. To fast computation, we used feature points each images and to phase agreement between two different image, we performed non-rigid registration. To validation our proposed method, we produced a coronary artery phantom, and the result of the registration has 1.9332mm average distance error.